EFFECT OF CULTIVATED PASTURE AND INTENSIVE FATTENING ON CARCASS TRAITS AND MEAT QUALITY OF AWASSI LAMBS - Ayhan Ceyhan; Mustafa Avci; Mehmet Mustafa Tanrikulu; Mubeen Ul Hassan; Martyna Wilk; Muhammad Umair Asghar (Journal of Animal and Plant Sciences, 2024)
The study aimed to evaluate the carcass trait, meat quality and fatty acid profile of Awassi lambs under cultivated pasture fattening with a concentrated feed (CPF) and intensive fattening (IF) system. A total of 76 male Awassi lambs (36 lambs in the CPF group and 40 in the IF group, 85 days average age) were distributed in complete random design into two experimental groups. The final body weight was lower, but the average daily gain was higher for the lambs on the CPF compared to the lambs on the IF system. There were no significant differences (p>0.05) between CPF and IF system for dressing percentage (50.31 and 51.51%) and shrinkage loss (3.45 and 2.50%), pelvic limb (34.9 and 30.3%), thoracic limb (20.8 and 18.3%), flank (9.4 and 7.6% ), neck (4.4 and 5.9%), and LTL section area (15.6 and 13.0 cm2), except for ribs (25.0 and 33.7%), which were higher in the intensive system. Also, meat pH and color value were not changed by the fattening systems. The fatty acid profile of the longissimus thoracis et lumborum muscles was assessed. The significant differences between groups were noted in margaric (1.00 and 1.80), heptadecenoic (0.51 and 0.99), eicosenoic (80.14 and 0.20), and linolenic fatty acids (0.21 and 0,19). In conclusion, the results of this study imply that carcass traits and meat quality were similar between CPF and IF systems in Awassi male lambs.
Keywords: Awassi lamb; carcass traits; cultivated pasture; fatty acid; intensive fattening; meat quality